Forced to Reimagine: Reflections on the Experience of Leicester Vaughan College Community Benefit Society - Miriam Gill; Lucy Faire (Education Sciences)
This article outlines the experiences of two tutors from an adult education department shut down by its higher education institution (HEI). It is a chronological reflective account of how members of the department responded to their exclusion by re-establishing their provision as a cooperative community benefit society (CBS), Leicester Vaughan College (LVC). This response was not only an expression of resistance, but it was an antidote to the neoliberal university system, which all too often undervalues adult education, marginalises adult learners or excludes their education altogether. As educators and students together, the aim was to use our understanding of the processes and practices of higher adult education to reconstruct this provision in a collaborative and cooperative way. Our experience before and after ‘expulsion’, and the reimagination of an alternative future in contrast to the dominant neoliberal model, shines a light on the wider difficulties and inequalities in the HE sector. As we searched (and continue to search) for a ‘happy ending’ with LVC, the multiple hurdles experienced exemplify the difficulties of trying to create a space for a new paradigm within hostile, shifting structures shaped by neoliberal regulatory and economic imperatives. This article finishes by setting out a context in which adult HE and institutions like LVC could flourish.